PENGARUH DOSIS KAPUR TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS KACANG HIJAU (Vigna radiate L.) - Cinta, Mutiara; Asfaruddin; Mulatsih, Sri (University of Prof. Dr. Hazairin, SH, 2024)
This research aimed to determine the effect of doses of dolomite lime and three varieties on the growth and yield of green bean plants. This research was carried out from May to July 2023, at Jalan Siti Khodijah Pondok Besi, Teluk Segara District, Bengkulu City, Bengkulu Province. The design used is a Divided Plot Design as the main plot is a dose of dolomite lime with 3 levels, namely D1 = Non-Lime, D2 = 1 x Al dd, D3 = 2 x Al dd. The subplots are varieties V1=Vima Varieties – 1, V3=Vima Varieties – 3, V5=Vima Varieties – 5. The research data was tested by analysis of variance followed by Duncan's Multiple Ranger test (DMRT) with a level of 5%. The research results showed that lime (Dolomite) treatment significantly affected plant height at 6 WAP, number of branches at 6 WAP, number of pods/plant, and yield/plot. The dose of lime (D3) provides the highest growth and yield in green beans. Meanwhile, the Variety treatment and the interaction between variety and lime dose had no significant influence on all the variables observed.